2020
DOI: 10.1101/2020.02.11.20021493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the accuracy of different respiratory specimens in the laboratory diagnosis and monitoring the viral shedding of 2019-nCoV infections

Abstract: 1 BackgroundThe outbreak of novel coronavirus pneumonia (NCP) caused by

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
708
2
15

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 665 publications
(768 citation statements)
references
References 12 publications
31
708
2
15
Order By: Relevance
“…Nasopharyngeal swabs and sputum have been suggested to be effective clinical samples for diagnosis (27,28), and we have assessed direct PCR using these matrices. It should be feasible to extend this to other common samples used for Covid- Covid-19 infection can be confirmed in less than an hour after sample collection and addition to mastermix for amplification and detection.…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal swabs and sputum have been suggested to be effective clinical samples for diagnosis (27,28), and we have assessed direct PCR using these matrices. It should be feasible to extend this to other common samples used for Covid- Covid-19 infection can be confirmed in less than an hour after sample collection and addition to mastermix for amplification and detection.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al [1] similarly considered 167 infected patients of whom 5 (3%) tested negative by RT-PCR at initial presentation. Fang et al [3] found that RT-PCR was only able to identify 36/51 (71%) of SARS-CoV-2 infected patients when using swabs taken 0-6 days after the onset of symptoms, and Luo et al [9] similarly reported that the initial sensitivity of throat swabs in secondary contacts was 71%.…”
Section: Introductionmentioning
confidence: 99%
“…To fight against COVID-19 and promote the prevention and control of the epidemic, researchers have recently made efforts in various aspects; their research involves epidemiological research 5,6,7 , diagnostic methods of the novel coronavirus 8,9,10,11 , clinical characteristics of the disease 12,13,14,15,16 , characteristics of disease transmission 17,18,19 , development of candidate therapies 20,21,22 , the identification of animal hosts 23,24,25,26 , etc. However, there has been no research conducted on the public's attention to COVID-19.…”
Section: Introductionmentioning
confidence: 99%